PENGARUH STORE ATMOSPHERE TERHADAP CUSTOMER LOYALTY KIBOU COFFEE KEMANG, JAKARTA - Alif Tamir; Muhammad Rizal; Lina Auliana (JURNAL LENTERA BISNIS, 2024)
Business competition may not be separated from now, judging from the growth of coffee shops that are mushrooming in the Jakarta area and other big cities. Because of the many coffee shops that already exist, as a businessman it is important to innovate to stay ahead of its competitors, the success of a store's excellence can be seen from how loyal its consumers are, because stores that can maintain consumer loyalty will get long-term success. One of the influences is the atmosphere of the store, therefore the researcher wants to analyze this phenomenon in the Kibou coffee shop with a quantitative method of correlation to obtain data to find the relationship between these two variables studied, so that we can find out how much of a relationship there is between the atmosphere of the store and consumer loyalty.